2019
DOI: 10.1111/gcb.14661
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dynamics, net primary productivity and human‐appropriated net primary productivity across a forest–cocoa farm landscape in West Africa

Abstract: Terrestrial net primary productivity (NPP) is an important metric of ecosystem functioning; however, there are little empirical data on the NPP of human‐modified ecosystems, particularly smallholder, perennial crops like cocoa (Theobroma cacao), which are extensive across the tropics. Human‐appropriated NPP (HANPP) is a measure of the proportion of a natural system's NPP that has either been reduced through land‐use change or harvested directly and, previously, has been calculated to estimate the scale of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 59 publications
1
37
1
Order By: Relevance
“…Calculations described by Morel et al (2019) indicate that HANPP for cocoa could be estimated with relatively high accuracy from cocoa tree density and number of shade trees (Figure 5). Values for HANPP varied from −4.6 to 5.2 Mg C ha-1 yr-1 or across the plots, with the negative values being recorded at a particularly shade-tree dense, young cocoa farm, and an older farm managed largely for timber.…”
Section: Hanpp Calculations Measures Of Hanpp For Cocoamentioning
confidence: 99%
See 4 more Smart Citations
“…Calculations described by Morel et al (2019) indicate that HANPP for cocoa could be estimated with relatively high accuracy from cocoa tree density and number of shade trees (Figure 5). Values for HANPP varied from −4.6 to 5.2 Mg C ha-1 yr-1 or across the plots, with the negative values being recorded at a particularly shade-tree dense, young cocoa farm, and an older farm managed largely for timber.…”
Section: Hanpp Calculations Measures Of Hanpp For Cocoamentioning
confidence: 99%
“…In order to determine the HANPP of such a mosaic landscape, detailed measures of HANPP of cocoa must be determined. Recent work by Morel et al (2019) generated detailed site-level data of NPP and HANPP in cocoa farms in the Central Region of Ghana. The study reported a strong relationship between cocoa farm characteristics, namely shade tree density and cocoa tree density, and HANPP.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations